(untitled) (KONFERENSIYA, 2025)
This article explores the application of the phonetic principle, a cornerstone of language instruction within the globally esteemed and results-proven Montessori methodology. The study details specific techniques for teaching alphabet recognition and word decoding within the Montessori approach to effectively facilitate English reading acquisition. Particular emphasis is placed on instructional methods utilizing phonetic segmentation models, including VC (Vowel-Consonant) and CVC (Consonant-Vowel-Consonant) patterns. The article argues that this structured phonetic foundation, aligned with the child’s developmental stages, fosters rapid development of phonemic awareness, independent reading skills, and a solid base for vocabulary expansion and advanced language competencies